A coupled THM finite element formulation for unsaturated soils and a strategy for its nonlinear solution. (August 2021) - Potts, David M.; Cui, Wenjie; Zdravković, Lidija
Abstract: This paper presents a coupled thermo-hydro-mechanical (THM) finite element (FE) formulation which is capable of accounting for the effects of temperature change on the behaviour of unsaturated soils. Both vapour flow and density variation are taken into account in the development of this formulation. The full derivation procedure is provided and the adopted assumptions are stated and explained. To improve the efficiency of the nonlinear solution process while maintaining the accuracy of the prediction, a novel approach for determining iterative corrections when modelling coupled transient problems with the Newton-Raphson algorithm is established and presented here. The performance of the proposed FE formulation and of the new strategy for iterative corrections in a nonlinear solver is subsequently demonstrated and verified by simulations of laboratory experiments on unsaturated compacted bentonite, showing good agreement between the numerical and experimental results.